2018
DOI: 10.5430/jnep.v8n12p36
|View full text |Cite
|
Sign up to set email alerts
|

Use of group discussion as an educational strategy during nursing appointments for patient undergoing bariatric surgery

Abstract: Objective: The purpose of this study was to describe a health education meeting based on group discussion during a nursing appointment with patients who are waiting to perform bariatric surgery. Methods: This is an exploratory study with a qualitative approach performed in July 2017 at a referral hospital in the State of Ceará-Brazil in the performance of bariatric surgeries. Twelve subjects participated and the data collection took place through self-completion of a semi-structured interview. Data analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…This reveals that the participants know the theme addressed, arising from the guidelines received at the institution and from living with other postoperative patients during monthly meetings. More and more, the population has been searching for information about bariatric surgery on the internet and with friends, to understand more about the procedure and the necessary care (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reveals that the participants know the theme addressed, arising from the guidelines received at the institution and from living with other postoperative patients during monthly meetings. More and more, the population has been searching for information about bariatric surgery on the internet and with friends, to understand more about the procedure and the necessary care (6) .…”
Section: Discussionmentioning
confidence: 99%
“…To meet the educational needs of this public, the technological resource created and validated, entitled "Bariatric surgery: care for a healthy life", stands out, which guides and encourages adherence to care in the perioperative period (6) . In a previous study, it was shown to be suitable for use by health professionals with candidates for bariatric surgery (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Em cada encontro, os participantes realizavam a leitura individual da cartilha, seguida pela avaliação da pesquisadora que questionava a presença de dúvidas sobre o conteúdo entre os participantes. A cartilha educativa "Cirurgia bariátrica: cuidados para uma vida saudável" foi desenvolvida durante mestrado em Enfermagem na Universidade Federal do Ceará e teve como etapas para sua construção: (9,10) revisão integrativa sobre cuidados no perioperatório da cirurgia bariátrica, busca em blogs de pacientes sobre as principais dúvidas relacionadas à cirurgia bariátrica e grupo focal com pacientes do pré e pós-operatório. Já na validação de conteúdo, contou com a participação de 42 profissionais de saúde mediante a técnica Delphi, além de validação de aparência com pacientes e designers gráficos.…”
Section: Intervenção Educativa Para O Grupo Intervençãounclassified
“…O conteúdo da cartilha envolve temáticas como dieta saudável no pré-operatório, prática de exercícios físicos, estratégias de controle de estresse, exames necessários para a realização da cirurgia, técnicas cirúrgicas, complicações, riscos e cuidados em cada fase do perioperatório. (10,11) A cartilha impressa vem sendo distribuída gratuitamente pela instituição em estudo e também via email através de email para profissionais de saúde e instituições.…”
Section: Intervenção Educativa Para O Grupo Intervençãounclassified